Hubungan Antara Usia Anak Dan Kebutuhan Perawatan Ortodonti Interseptif (Kajian Pada Anak Usia 8 – 11 Tahun di SDN Balekambang 03 Jakarta Timur) - Klara Angelina Carisa; Yohana Yusra; Magdalena Juliani Hardja Buntara (Fakultas Kedokteran Gigi Universitas Trisakti, 2019)
Background: interceptive orthodontic treatment is one of orthodontic treatment could be used to control and prevent increasing malocclusion prevalence. Interceptive orthodontic treatment prevents increasing severity of malocclusion which begin in mixed dentition stage. Interceptive orthodontic treatment needs can be measured by using Interceptive Orthodontic Care Neeeds Index (IOCNI). Assessment of this index given quantitatively by scoring on indicator. The aim of this study is to determine the relationship between children’s age and interceptive orthodontic treatment needs of 8 – 11 years old student in 03 Government Elementary School, Balekambang, East Jakarta. Materials and Methods: intraoral examination was done on subjects by a dentist. Score given on each indicator based on intraoral condition. Scoring data calculated to determine subject’s grade of orthodontic treatment need. This is an observartional-analytic study with cross-sectional design. Results: 172 students were examined which consist of 2 children aged 8 years old, 34 children aged 9 years old, 75 children aged 10 years old and 61 children aged 11 years old. Examination obtains that 11,05% children don’t need orthodontic treatment, 59,30% children needed interceptive orthodontic treatment, and 27,9% children need corrective orthodontic treatment. Interceptive orthodontic treatment mostly needed by 10 years old children (27,9%). Caries on second deciduous molar, early loss of second deciduous molar, and anterior crowding both on upper and lower jaw are highly presented as dental malocclusion abnormalities on subjects. Conclusion: this study showed no significant correlation (p = 0,861) between children’s age and interceptive orthodontic treatment need.